A critical review on experimental investigation and finite element analysis on structural performance of kenaf fibre reinforced concrete - Solahuddin, Azuwa (Institution of Structural Engineers, 2022)
Kenaf fibre is highly useful material. According to many research works, its consumption could be used either in concrete or reinforced concrete mixtures to improve structural performance. Furthermore, it was essential for summarising the recent findings and gaps regarding the effect of kenaf fibre as an additive in different volume fractions on various concrete and reinforced concrete hardened properties. This review paper examines the recent investigations on the effect of kenaf fibre usage on the structural performance of reinforced concrete based on many previous studies. This is followed by a discussion on the structural performance of kenaf fibre based on experimental study and finite element analysis. The literature reviews indicated that the use of kenaf fibre at certain volume fractions improves the concrete compressive strength, flexural strength, and splitting tensile strength. Moreover, the reinforced concrete structural performance on young modulus, load–deflection, ultimate load capacity, crack pattern, and the failure mode is improved with kenaf fibre inclusion using the experimental method and finite element analysis. The structural performance of reinforced concrete improvement is attributed to proprietary urethane-based surface treatment, which is developed by improving the bond between kenaf fibre and cement matrix based on the scanning electron microscope. Notably, although the application of concrete in the construction industry would be possible with the use of kenaf fibre in it, further research about it should be conducted.